Sponsored links: Algebra eBooks
 

Related

breakup-false-solve

eq1:x^3+x-2*y=0;

breakup: false;

solve(eq1,x);

Calculate

breakup-false-matrix-programmode-solve-true

programmode: false;

breakup: true;

eq1:0=I0-U1/R1-(U1-U2...

Calculate

breakup-false-matrix-programmode-solve-true

programmode: false;

breakup: true;

eq1:0=I0-U1/R1-(U1-U2...

Calculate

breakup-false-programmode-solve-true

eq1:V = F * ((C*(1 - ...

programmode: false;

breakup: true;

Calculate

breakup-false-programmode-solve-true

eq1:V = F * ((C*(1 - ...

programmode: false;

breakup: true;

Calculate

breakup-false-matrix-programmode-solve-true

programmode: false;

breakup: true;

eq1:0=I0-U1/R1-(U1-U2...

Calculate

breakup-false-fortran-matrix-programmode-solve-true

programmode: false;

breakup: true;

eq1:0=I0-U1/R1-(U1-U2...

Calculate

breakup-solve

eq1:V = F * ((C*(1 - ...

breakup:falseres:solv...

Calculate

breakup-fortran-matrix-solve-true

breakup: true;

eq1:0=I0-U1/R1-(U1-U2...

eq2:0=I0-U2/R2-(U2-U1...

Calculate

breakup-false-programmode-solve-true

programmode: false;

breakup: true;

solve (x^3 + x^2 - 1);

Calculate

breakup

Run Example
(%i1)eq1:V = F * ((C*(1 - (1/(1 + Y))^(M*H)) / H*Y) + (1 / (1 + Y))^(M*H));
                                                    1
                                       C Y (1 - ----------)
                                                       H M
                              1                 (Y + 1)
(%o1)              V = F (---------- + --------------------)
                                 H M            H
                          (Y + 1)
(%i2) breakup:falseres:solve(eq1, Y);
                                          H M
                               H V (Y + 1)    - F H
(%o2)                     [Y = --------------------]
                                          H M
                               C F (Y + 1)    - C F
(%i3) 
Run Example
programmode: false;
(%o1)                                false
(%i2) breakup: true;
(%o2)                                true
(%i3) eq1:0=I0-U1/R1-(U1-U2)/R12-(U1-U3)/R13;
                            U3 - U1   U2 - U1   U1
(%o3)                   0 = ------- + ------- - -- + I0
                              R13       R12     R1
(%i4) eq2:0=I0-U2/R2-(U2-U1)/R12-(U2-U3)/R23;
                            U3 - U2   U2   U1 - U2
(%o4)                   0 = ------- - -- + ------- + I0
                              R23     R2     R12
(%i5) eq3:0=I0-U3/R3-(U3-U1)/R13-(U3-U2)/R23;
                             U3   U2 - U3   U1 - U3
(%o5)                  0 = - -- + ------- + ------- + I0
                             R3     R23       R13
(%i6) a:matrix(solve([eq1,eq2,eq3],[U1,U2,U3]));
Solution:

(%t6) U2 = (R13 (I0 R1 (3 R2 R3 + 2 R2 R23) + I0 R12 (2 R2 R3 + R2 R23))
 + R12 (I0 R1 (3 R2 R3 + R2 R23) + I0 R2 R23 R3) + 3 I0 R1 R2 R23 R3)
/(R13 (R12 (R3 + R23 + R2) + R1 (R3 + R23 + R2) + R2 R3 + R2 R23)
 + R12 (R1 (R3 + R23 + R2) + R23 R3 + R2 R3) + R1 R23 (R3 + R2) + R2 R23 R3)

(%t7) U3 = (R13 (I0 R1 (R23 R3 + 3 R2 R3) + I0 R12 (R23 R3 + 2 R2 R3)
 + I0 R2 R23 R3) + I0 R1 R12 (2 R23 R3 + 3 R2 R3) + 3 I0 R1 R2 R23 R3)
/(R13 (R12 (R3 + R23 + R2) + R1 (R3 + R23 + R2) + R2 R3 + R2 R23)
 + R12 (R1 (R3 + R23 + R2) + R23 R3 + R2 R3) + R1 R23 (R3 + R2) + R2 R23 R3)

(%t8) U1 = (R13 (I0 R1 (3 R2 R3 + 2 R2 R23) + I0 R1 R12 (R3 + R23 + R2))
 + I0 R1 R12 (2 R23 R3 + 3 R2 R3) + 3 I0 R1 R2 R23 R3)
/(R13 (R12 (R3 + R23 + R2) + R1 (R3 + R23 + R2) + R2 R3 + R2 R23)
 + R12 (R1 (R3 + R23 + R2) + R23 R3 + R2 R3) + R1 R23 (R3 + R2) + R2 R23 R3)
(%o8)                         [ [%t6, %t7, %t8] ]
(%i9) a[1];
(%o9)                          [[%t6, %t7, %t8]]
(%i10) 
Run Example
breakup: true;
(%o1)                                true
(%i2) eq1:0=I0-U1/R1-(U1-U2)/R12-(U1-U3)/R13;
                            U3 - U1   U2 - U1   U1
(%o2)                   0 = ------- + ------- - -- + I0
                              R13       R12     R1
(%i3) eq2:0=I0-U2/R2-(U2-U1)/R12-(U2-U3)/R23;
                            U3 - U2   U2   U1 - U2
(%o3)                   0 = ------- - -- + ------- + I0
                              R23     R2     R12
(%i4) eq3:0=I0-U3/R3-(U3-U1)/R13-(U3-U2)/R23;
                             U3   U2 - U3   U1 - U3
(%o4)                  0 = - -- + ------- + ------- + I0
                             R3     R23       R13
(%i5) a:matrix(solve([eq1,eq2,eq3],[R12,R23,R13]));
(%o5)                   [ [R12 = 0, R23 = 0, R13 = 0] ]
(%i6) fortran(a);
      a(1,1) = [R12 = 0,R23 = 0,R13 = 0]
(%o6)                                done
(%i7) 

Related Help

Help for Breakup